cGAS-STING signaling pathway in intestinal homeostasis and diseases - Yang, Yuchen; Wang, Li; Peugnet-González, Ivonne; Parada-Venegas, Daniela; Dijkstra, Gerard; Faber, Klaas Nico (Frontiers in Immunology, 2023)
The intestinal mucosa is constantly exposed to commensal microbes, opportunistic pathogens, toxins, luminal components and other environmental stimuli. The intestinal mucosa consists of multiple differentiated cellular and extracellular components that form a critical barrier, but is also equipped for efficient absorption of nutrients. Combination of genetic susceptibility and environmental factors are known as critical components involved in the pathogenesis of intestinal diseases. The innate immune system plays a critical role in the recognition and elimination of potential threats by detecting pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs). This host defense is facilitated by pattern recognition receptors (PRRs), in which the cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway has gained attention due to its role in sensing host and foreign double-stranded DNA (dsDNA) as well as cyclic dinucleotides (CDNs) produced by bacteria. Upon binding with dsDNA, cGAS converts ATP and GTP to cyclic GMP-AMP (cGAMP), which binds to STING and activates TANK binding kinase 1 (TBK1) and interferon regulatory factor 3 (IRF3), inducing type I interferon (IFN) and nuclear factor kappa B (NF-κB)-mediated pro-inflammatory cytokines, which have diverse effects on innate and adaptive immune cells and intestinal epithelial cells (IECs). However, opposite perspectives exist regarding the role of the cGAS-STING pathway in different intestinal diseases. Activation of cGAS-STING signaling is associated with worse clinical outcomes in inflammation-associated diseases, while it also plays a critical role in protection against tumorigenesis and certain infections. Therefore, understanding the context-dependent mechanisms of the cGAS-STING pathway in the physiopathology of the intestinal mucosa is crucial for developing therapeutic strategies targeting the cGAS-STING pathway. This review aims to provide insight into recent findings of the protective and detrimental roles of the cGAS-STING pathway in intestinal diseases.